Risk preferences and prenatal exposure to sex hormones for ladinos (2014)
Risk preferences drive much of human decision making including investment, career and health choices and many more. Thus, understanding the determinants of risk preferences refines our understanding of choice in a broad array of environments. We assess the relationship between risk preferences, prenatal exposure to sex hormones and gender for a sample of Ladinos, which is an ethnic group comprising 62.86% of the population of Guatemala. Prenatal exposure to sex hormones has organizational effects on brain development, and has been shown to partially explain risk preferences for Caucasians. We measure prenatal exposure to sex hormones using the ratio of the length of the index finger to the length of the ring finger (2D:4D), which is negatively (positively) correlated with prenatal exposure to testosterone (estrogen). We find that Ladino males are less risk averse than Ladino females, and that Ladino males have lower 2D:4D ratios than Ladino females on both hands. We find that the 2D:4D ratio does not explain risk preferences for Ladinos. This is true for both genders, and both hands. Our results highlight the importance of exploring the behavioral significance of 2D:4D in non-Caucasian racial groups.